1990
DOI: 10.1017/s0043174500056113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress, Nitrogen, and Gibberellic Acid on Fluazifop and Glyphosate Activity on Oats (Avena sativa)

Abstract: A series of experiments was carried out on oat to test the efficacies of fluazifop and glyphosate against water-stressed plants, plants grown in low and high nitrogen (N), and plants treated with gibberellic acid (GA). In the laboratory, plants maintained at wilting point for 5 days before and 9 days after spraying with fluazifop (0.5 kg ae/ha) appeared healthy 32 days after herbicide application, while plants supplied with water throughout the experiment were completely chlorotic/necrotic and had main stem de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
(84 reference statements)
4
26
0
1
Order By: Relevance
“…Therefore, they suggested that restricted translocation was the physiological mechanism explaining the lower efficacy and that the cause was lower carbon assimilation at low nitrogen supplies. Results from experiments with oat sprayed with fluazifop or glyphosate indicated the same mechanism (Dickson et al. , 1990).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, they suggested that restricted translocation was the physiological mechanism explaining the lower efficacy and that the cause was lower carbon assimilation at low nitrogen supplies. Results from experiments with oat sprayed with fluazifop or glyphosate indicated the same mechanism (Dickson et al. , 1990).…”
Section: Discussionmentioning
confidence: 96%
“…In the same study, it was observed that the susceptibility of A. theophrasti to atrazine did not change with nitrogen rate. Other studies have confirmed the interaction between herbicide efficacy and nitrogen application and have suggested that decreased translocation of herbicides out of treated leaves is the mechanism behind the interaction, but the results are equivocal and the interaction is not always evident (Dickson et al. , 1990; Kim et al.…”
Section: Introductionmentioning
confidence: 99%
“…(Rioux et al ., 1974; Lemerle & Verbeek, 1995). Particular variables of importance include soil moisture stress (Boydston, 1990; Dastgheib et al ., 1990; Dickson et al ., 1990; Lemerle & Verbeek, 1995), nitrogen deficiency (Dickson et al ., 1990), temperature, light, wind, humidity and rainfall (Muzik, 1975; Doran & Andersen, 1976; Coupland, 1983, 1984; Merritt, 1984; Nalewaja & Woznica, 1985; Jensen & Kudsk, 1988; Devine, 1989; Caseley, 1990; Wicks et al ., 1993; McMullan, 1994; Madafiglio et al ., 2000). As a general principle, a lower dose of herbicide may kill most of the target weeds under favourable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide efficacy as influenced by the N environment under which weeds were grown, however, has not been studied in the literature. Dickson et al (1990) reported that tame oats (Avena sativa L.) were more tolerant to fluazifop and glyphosate when grown under a low than a high N environment (1 vs. 10 mol N m Ϫ3 ). Although the effect of N on herbicide efficacy has been illustrated in tame oats, similar work has not been reported for weeds.…”
mentioning
confidence: 99%